2019
DOI: 10.21031/epod.583891
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Reliability of Teachers, Self and Peer Assessments at Primary School Level with Generalizability Theory

Abstract: This study aims at determining the reliability coefficients of teacher, self and peer assessments carried out at primary school level. In line with this aim, an interdisciplinary approach is adopted, and the notion of helpfulness included within the scope of values education is addressed in connection with the practices followed in Turkish, social studies and music lessons. The study group consists of 30 students of the third graders from a public school in the city of Ankara. In the light of the aim of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Children become aware of their learning problems by recognizing their strengths and weaknesses. They can produce solutions to their own learning problems by using the detailed information they have acquired about their own learning paths (Gürlen, Boztunç-Öztürk, & Eminoğlu, 2019). Children should be taught ways of selfevaluation so that the child can recognize himself, and this dimension should be included in pre-school education curricula.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Children become aware of their learning problems by recognizing their strengths and weaknesses. They can produce solutions to their own learning problems by using the detailed information they have acquired about their own learning paths (Gürlen, Boztunç-Öztürk, & Eminoğlu, 2019). Children should be taught ways of selfevaluation so that the child can recognize himself, and this dimension should be included in pre-school education curricula.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…On the other hand, accuracy of self-assessment for summative purposes has been argued because of some reliability issues (Brooks, 2002;Brown, Andrade and Chen, 2015). When comparing to teacher assessment and peer assessment, raters are generally more generous with self-assessment (Gürlen, Boztunç Öztürk, & Eminoğlu, 2019;Karakaya, 2015). The research studies showed that some relationship exists between self-assessment and students' academic achievement (Brown & Harris, 2013;.…”
Section: Introductionmentioning
confidence: 99%